2021
DOI: 10.1029/2020jc016871
|View full text |Cite
|
Sign up to set email alerts
|

The Shelf Circulation of the Bellingshausen Sea

Abstract: Oceanic processes in the Southern Ocean and along the Antarctic margins influence Earth's climate on a global scale. The upper Southern Ocean has persistently warmed over the last century (Gille, 2008), which has been accompanied by an increase in heat content of the West Antarctic continental shelf (Schmidtko et al., 2014) and by increased glacial melting (Cook et al., 2016;Pritchard et al., 2012). The thinning of floating ice shelves throughout West Antarctic coastal seas, which includes the Amundsen and Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(35 citation statements)
references
References 75 publications
(161 reference statements)
7
28
0
Order By: Relevance
“…S4). Last, the model successfully reproduces main shelf/slope circulation patterns, such as the strength and structure of the AACC (see below) and CDW intrusions in the Amundsen and Bellingshausen Seas as shown in observations (56,57).…”
Section: Model Evaluationmentioning
confidence: 65%
See 1 more Smart Citation
“…S4). Last, the model successfully reproduces main shelf/slope circulation patterns, such as the strength and structure of the AACC (see below) and CDW intrusions in the Amundsen and Bellingshausen Seas as shown in observations (56,57).…”
Section: Model Evaluationmentioning
confidence: 65%
“…In addition, we perform a comparison of conductivity-temperature-depth (CTD) profiles and model output in the Bellingshausen Sea from a hydrographic cruise ( 56 ) performed in January 2019 (fig. S5).…”
Section: Methodsmentioning
confidence: 99%
“…In order to establish whether water mass properties found in GLORYS are representative of conditions in the Bellingshausen and Amundsen seas, we compare the model output with existing hydrographic observations from these shelf seas. Previously observed hydrographic transects crossing the Belgica and Latady troughs in 2007 and 2018/19 (Ruan et al, 2021;Schulze-Chretien et al, 2021) show similar characteristics to GLORYS for the zonal transect in the warm regime (Fig. 9a), where mCDW occupies the lower layers of the water column from 300 m to the seabed with similar water mass properties and maximum temperatures of up to 1.6 • C. Jenkins et al (2018), on the other hand, observed the water mass stratification in a cold year near Dotson ice shelf in the Amundsen Sea, which indicated that mCDW is only present in lower layers of the water column reaching from 700 to almost 1000 m. These findings are substantially different to the water mass stratification of cold years presented by GLORYS in the Bellingshausen Sea, where both transects (meridional and zonal) show mCDW higher up in the water column with uplifted 27.6 kg m −3 and 27.8 kg m −3 isopycnals in the southern and central Bellingshausen Sea in the cold regime.…”
Section: Accepted Articlementioning
confidence: 92%
“…Assmann et al (2005), using coupled ice-ocean simulations, also found the region to be dominated by a cyclonic gyre with a similar longitudinal extent as in GLORYS. Moreover, recent studies observed individual cyclonic circulation features within the major troughs of the Bellingshausen Sea with inflow of mCDW along the eastern boundaries of the troughs up to the ice shelves (Schulze-Chretien et al, 2021;Zhang et al, 2016).…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation